16S rRNA V4 gut microbiome of Leptonycteris yerbabuenae in Mexico - Viquez-R, Luis (Dryad, 2021)
Migratory animals live in a world of constant change. Animals undergo many
physiological changes preparing themselves for the migration. Although
this field has been extensively studied over the last decades, we know
relatively little about the seasonal changes that occur in the microbial
communities that these animals carry in their guts. Here we assessed the
V4 region of the 16S rRNA high-throughput sequencing data as a proxy to
estimate microbiome diversity of Tequila Bats from fecal pellets and
evaluate how the natural process of migration shapes the microbiome
composition, and diversity. We collected samples from individual bats at
two localities in the Dry Forest biome (Chamela and Coquimatlán) and one
site at the end point of the migration in the Sonoran Desert (Pinacate).
We found that the gut microbiome of the Tequila bats is largely dominated
by Firmicutes and Proteobacteria. Our data also provide insights on how
microbiome diversity shifts at the same site in consecutive years. Our
study has demonstrated that both locality and year-to-year variation
contribute to shaping the composition, overall diversity, and the
'uniqueness' of the gut microbiome of migratory nectar-feeding
female bats with localities from the dry forest biome looking more like
each other when compared to the desert biome. In terms of beta diversity,
our data show a stratified effect in which the samples locality was the
strongest factor influencing the gut microbiome, but with significant
variation between consecutive years at the same locality.
See the Viquez-R et al 2021 for more information. DOI:10.1128/Spectrum.01525-21
Keywords: FOS: Biological sciences; Illumina MiSeq platform; 16S rDNA; Microbiome; Chiroptera; Gut microbiome; Sonora; Chamela; Coquimatlan